2010
DOI: 10.2196/jmir.1426
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Virtual Worlds for Scenario-Based Repeated Team Training of Cardiopulmonary Resuscitation in Medical Students

Abstract: BackgroundContemporary learning technologies, such as massively multiplayer virtual worlds (MMVW), create new means for teaching and training. However, knowledge about the effectiveness of such training is incomplete, and there are no data regarding how students experience it. Cardiopulmonary resuscitation (CPR) is a field within medicine in high demand for new and effective training modalities.ObjectiveIn addition to finding a feasible way to implement CPR training, our aim was to investigate how a serious ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 86 publications
(82 citation statements)
references
References 27 publications
(23 reference statements)
6
74
0
2
Order By: Relevance
“…The feasibility of VWs to train and evaluate health professionals and students has been investigated in cardiopulmonary resuscitation training, operating theater induction, decision-making skills, diabetes management, and teamwork in emergency situations (27)(28)(29)(30)(31). Moreover, the Virtual Association of Surgeons has successfully held a conference in the VW attended by numerous members from five countries (32).…”
Section: Virtual Worldsmentioning
confidence: 99%
“…The feasibility of VWs to train and evaluate health professionals and students has been investigated in cardiopulmonary resuscitation training, operating theater induction, decision-making skills, diabetes management, and teamwork in emergency situations (27)(28)(29)(30)(31). Moreover, the Virtual Association of Surgeons has successfully held a conference in the VW attended by numerous members from five countries (32).…”
Section: Virtual Worldsmentioning
confidence: 99%
“…In 2010, a study investigated the effectiveness of multiplayer virtual worlds using avatars in CPR training of medical students. The research showed promising results about resuscitation training efficacy but also the satisfaction of the participants was quite high [29]. In 2012, groups of pre-clinical medical students were pre-trained on CPR performance using serious game technology.…”
Section: Discussionmentioning
confidence: 96%
“…Cardiopulmonary resuscitation [26,27] Massively multiplayer virtual world A test-retest (6-month interval between sessions) Educacionais Online virtual patients [28] The Clinical Health Economics System Simulation (CHESS) [29] Computerized team-based quasi-competitive simulator Tabela 1: Exemplos de simuladores para a área da saúde.…”
Section: Historicamentementioning
confidence: 99%